Hubungan Anxiety Disorder dengan Kualitas Tidur Mahasiswa dalam Menghadapi Ujian Objective Structured Clinical Examination (OSCE) - Eillen Duhita; Yusrika Yusrika; Saufa Sarah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Anxiety is an excessive state of tension characterized by feelings due to a response to stress or conflicting conditions. This study aims to investigate the relationship between anxiety disorders and sleep quality among nursing students during the Objective Structured Clinical Examination (OSCE) in the Diploma III Nursing Program, Faculty of Health Sciences, Abulyatama University. This study consisted of 168 individuals. The sample was 65 respondents selected using a purposive sampling technique. The research was conducted from July 25th to 29th, 2025. This study employed a descriptive analytical method with a cross-sectional approach. The research instruments were the Zung Self-Rating Anxiety Scale (ZSAS) and the Pittsburgh Sleep Quality Index (PSQI). The data was analyzed using the Chi-Square test. The research results indicated a significant relationship between anxiety disorders and the sleep quality of students during the OSCE at the Diploma III Nursing Program, Abulyatama University, with a p-value of 0.025 (p < 0.05). Based on this finding, this study proves a relationship between anxiety disorders and sleep quality among the Diploma III students during the OSCE preparation. This study suggests that students and the university provide counselling sessions before the test to reduce the effects of anxiety disorders in students. Therefore, this study serves as a resource to raise awareness on how to manage emotions during exam preparation.